2020
DOI: 10.1371/journal.pbio.3000719
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of genes required for body axis and limb formation by global identification of retinoic acid–regulated epigenetic marks

Abstract: Identification of target genes that mediate required functions downstream of transcription factors is hampered by the large number of genes whose expression changes when the factor is removed from a specific tissue and the numerous binding sites for the factor in the genome. Retinoic acid (RA) regulates transcription via RA receptors bound to RA response elements (RAREs) of which there are thousands in vertebrate genomes. Here, we combined chromatin immunoprecipitation sequencing (ChIP-seq) for epigenetic mark… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 86 publications
5
41
0
Order By: Relevance
“…Recently, ChIP-seq (H3K27ac and H3K27me3) analysis combined with RNA-seq analysis performed on wild-type vs. Aldh1a2-/- trunk tissue found that the previously known RARE upstream of Fgf8 is normally marked by H3K27me3, but this mark is lost in the RA-deficient mutant [ 36 ]. In this study, two additional RAREs near Fgf8 were also found to be marked by H3K27me3 when RA is present, highlighting the existence of additional potential Fgf8 RARE silencers that can be further studied to pursue the mechanism underlying RA repression of Fgf8 in heart tissues compared to caudal tissues already examined [ 33 , 34 ].…”
Section: Requirement Of Retinoic Acid For Forelimb Bud Initiationmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, ChIP-seq (H3K27ac and H3K27me3) analysis combined with RNA-seq analysis performed on wild-type vs. Aldh1a2-/- trunk tissue found that the previously known RARE upstream of Fgf8 is normally marked by H3K27me3, but this mark is lost in the RA-deficient mutant [ 36 ]. In this study, two additional RAREs near Fgf8 were also found to be marked by H3K27me3 when RA is present, highlighting the existence of additional potential Fgf8 RARE silencers that can be further studied to pursue the mechanism underlying RA repression of Fgf8 in heart tissues compared to caudal tissues already examined [ 33 , 34 ].…”
Section: Requirement Of Retinoic Acid For Forelimb Bud Initiationmentioning
confidence: 99%
“…In addition, no change in Meis2 expression in the interdigital tissues of the mouse was found in Rdh10 mutants lacking limb RA signaling [ 40 ]. Prior to forelimb bud initiation, RA is also not essential for Meis1/2 expression in trunk lateral plate mesoderm that gives rise to limb buds, but loss of RA does reduce Meis1/2 expression in somites [ 14 , 36 ].…”
Section: Requirement Of Meis Genes For Forelimbmentioning
confidence: 99%
See 3 more Smart Citations